Hubungan Sektor Pertanian dan Industri Pengolahan serta Faktor-faktor yang Mempengaruhinya - Hermawan, Heri (Jurnal Trikonomika, 2010)
One of the successful economic development indicators indicated by its economic growth which was than followed by the change in its economic structure. Structural change of the economy where the role of agriculture will be shifted to industry will be indicated by the shift of the national income as well as the shift in the labors employed. However, for such a case in Indonesia, most of the labors employed are still in agriculture. For those reasons, economic development in this country should be more emphasized upon agriculture, supported by the growth of its processing industries. Based on those condition, this research questions that would be explored were: what was the effect of the growth in agricultural processing industries, number of labor, education, investment, as well as its export and import upon the growth of agricultural sectors. The simultaneous model was used to analyze research question identified. The results of this study indicated that the growth of agricultural sector were significantly affected by the growth of investment in this sector, the growth of average education level of the labors, opportunities of export market for agricultural products, and the growth of agricultural processing industries through the growth of its labors employed and their level of education as well.